1977
DOI: 10.1098/rstb.1977.0019
|View full text |Cite
|
Sign up to set email alerts
|

The genetic analysis of meiosis in female Drosophila melanogaster

Abstract: The three major features of meiosis are first synapsis, then exchange, and finally, disjunction of homologous chromosomes; these phenomena occur before pachytene, during pachytene, and after pachytene respectively. The effects of meiotic mutants, or other perturbations, either endogenous or exogenous, on the meiotic process may be assigned tentatively to one of these intervals, based on the earliest discernible abnormality. Thus mutants exhibiting abnormal disjunction and normal exchange affect post-pachytene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(65 citation statements)
references
References 46 publications
3
61
1
Order By: Relevance
“…As mentioned above, Drosophila shows a marked suppression of crossing over near the tip of the X chromosome, spanning megabases of sequence (Lindsley and Sandler 1977). In contrast, our subtelomeric data come from a physical region of $100 kb.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…As mentioned above, Drosophila shows a marked suppression of crossing over near the tip of the X chromosome, spanning megabases of sequence (Lindsley and Sandler 1977). In contrast, our subtelomeric data come from a physical region of $100 kb.…”
Section: Resultsmentioning
confidence: 80%
“…Moreover, it has recently been reported that nonhomologous end joining (NHEJ) is a frequently used double-strand break repair pathway at the ends of human chromosomes (Linardopoulou et al 2005). Interestingly, while yeast exhibits a moderate reduction of homologous recombination in a small region of the telomere, D. melanogaster shows a more dramatic, large-scale suppression of crossing over within and proximal to telomeres (Lindsley and Sandler 1977). The tip of the X chromosome (distal 5%), in particular, shows markedly reduced crossing over.…”
mentioning
confidence: 99%
“…The cytological localization of jba and pm provides clues to estimate the location of the Lhr locus. Genetic distances should be proportional to the cytological distance especially in the middle portion of a chromosome arm (Lindsley and Sandler, 1977). The genetic map distance between Lhr and jba is 12.9, and Regions at which recombination occurred are indicated as , region between sd and jba; , region between jba and pm.…”
Section: Resultsmentioning
confidence: 99%
“…Studies in fruit flies (Drosophila melanogaster) and other organisms have identified numerous genes with roles in homologous recombination (Lindsley and Sandler, 1977;Sekelsky et al, 2000). Among these are factors with a general role in homologous recombination including members of the Rad52 epistasis group such as the recombinase Rad51 (Ghabrial et al, 1998;Staeva-Vieira et al, 2003;Börner et al, 2004;McCaffrey et al, 2006).…”
Section: Introductionmentioning
confidence: 99%